(untitled) - Porter, Connie (Boston, 1991)
In her resonant first novel, Porter lays bare a modern social tragedy through a pointed, compassionate portrait of one family and their neighbors on crumbling All-Bright Court. Sam Taylor represents the scores of southern black men and families who migrated to the industrial North and the mythic promise of security and fulfillment. Sam, his wife Mary Kate, and their ever-growing family find in Buffalo what Tupelo would not offer: gas heat and running water, apparent social equality with European co-workers, and a privileged education for prematurely wise son Mikey. Porter, a survivor of Buffalo tenement life, reveals the betrayal of the Taylors by society, company, expectations, and even by racially confused Mikey, in this accomplished telling of a bittersweet story. Previewed in Prepub Alert, LJ 5/1/91.
Keywords: Steel industry and trade,African Americans,African American families,Thương mại và công nghiệp thép